Minimum wages for online labour platforms? - Wood, A; Anwar, M; Graham, M (Routledge, 2019)
The rise of the “gig economy” has enabled Internet users to find new work previously unavailable to them. The “online labor platforms”, which constitute a global remote gig economy, enable clients to access worldwide labor power. This chapter discusses how these platforms work. Two hundred and fifty remote gig economy workers across ten countries and four continents have been interviewed along with platform CEOs and government and trade union officials. Moreover, a survey encompassing 679 Asian and African workers has been conducted in addition to an analysis of transaction data and observation studies. The authors conclude by cautioning against having online gig work function as an unregulated labor market and propose some suggestions to improve relationships and conditions between the employing class, the governing class and the working class.